Pengaruh Partisipasi Anggaran Dan Akuntansi Pertanggungjawaban Terhadap Kinerja Manajerial Pada KSP. Kopdit Hiro Heling - Maria Venselina Nona Yeni; Henrikus Herdi; Emilianus Eo Kutu Goo (Journal of Creative Student Research, 2023)
This research aims to determine the effect of budget participation and responsibility accounting on managerial performance at KSP. Chief of Staff Hiro Heling. The type of research used in this research is quantitative associative research. The population in this study were all KSP employees. Kopdit Hiro Heling, with a sampling technique using a saturated sample so that the number of samples in this study amounted to 45 people. The data used in this study is primary data with data collection methods, namely questionnaires. Methods of data analysis using multiple linear regression analysis. The results showed that partially budgetary participation variables had an effect on managerial performance variables, responsibility accounting variables had an effect on managerial performance variables and budgetary participation and accountability accounting variables had an effect on managerial performance.